FGFBP1-mediated crosstalk between fibroblasts and pancreatic cancer cells via FGF22/FGFR2 promotes invasion and metastasis of pancreatic cancer. (12th June 2021) - Zhang, Zheng; Qin, Yi; Ji, Shunrong; Xu, Wenyan; Liu, Mengqi; Hu, Qiangsheng; Ye, Zeng; Fan, Guixiong; Yu, Xianjun; Liu, Wensheng; Xu, Xiaowu
Abstract: Fibroblast growth factor-binding protein 1 (FGFBP1) promotes fibroblast growth factor (FGF) activity by releasing FGFs from extracellular matrix storage. We previously reported that the tumor suppressor F-box and WD repeat domain-containing 7 suppresses FGFBP1 by reducing expression of c-Myc, which inhibits the proliferation and migration of pancreatic cancer cells. However, the potential mechanism by which FGFBP1 facilitates pancreatic ductal adenocarcinoma (PDAC) remains unexplored. In this study, we focused on the function of FGFBP1 in the interplay between cancer-associated fibroblasts (CAFs) and pancreatic cancer cells (PCCs). Decreased FGF22 expression was detected in CAFs co-cultured with PCCs with FGFBP1 abrogation, which was verified in the cell culture medium by enzyme-linked immunosorbent assay. Active cytokine FGF22 significantly facilitated the migration and invasion of PANC-1 and Mia PaCa-2 cells. The number of penetrating PCCs cocultured with CAFs with FGF22 abrogation was significantly less than that of the control group. Interestingly, higher expressions of FGF22 and fibroblast growth factor receptor 2 (FGFR2) were associated with worse prognosis of patients with PDAC and FGFR2, an independent prognostic marker of PDAC. The PANC-1 and Mia PaCa-2 cells with silenced FGFR2 showed weaker invasion and metastasis, even if these cells were simultaneously treated with cytokine FGF22. These results revealed that FGFBP1-mediated interaction between CAFs and PCCs via FGF22/FGFR2 facilitates the migration and invasion of PCCs. FGFR2 could act as a prognostic marker for patients with PDAC.